Performance management for different employee groups : a contribution to employment systems theory / Achim Krausert - Krausert, Achim
Presents a framework of analysis to capture and explain differences in employment systems. Taking account of the wealth of research in the field, this book provides a basis for developing function-specific performance management systems, integrating aspects such as incentivization, multi-source appraisal, and accountability.